The nucleotide sequence of the 16S ribosomal RNA gene of the archaebacterium Halococcus morrhua. - Leffers, H (1984)
The sequence of the 16S rRNA gene from the archaebacterium Halococcus morrhua was determined by the dideoxynucleotide sequencing method. It is 1475 nucleotides long. This is the second archaebacterial sequence to be determined and it provides sequence comparison evidence for the secondary structural elements confined to the RNAs of this kingdom and, also, support for controversial or additional base pairing in the eubacterial RNAs. Six structural features are localized that have varied during the evolution of the archaebacteria, eubacteria and eukaryotes. Moreover, although the secondary structures of both sequenced archaebacterial RNAs strongly resemble those of eubacteria, they contain sufficient eukaryotic-like structural characteristics to reinforce the view that they belong to a separate line of evolutionary descent.